Free Cash Flow, Kinerja Internal, Dan Pengaruhnya Terhadap Nilai Perusahaan - Irma Sari Permata; Nana Nawasiah; Trisnani Indriati (Liquidity: Jurnal Riset Akuntansi dan Manajemen, 2018)
The purpose of this study is to answer the phenomena that occur both theoretical phenomena and the empirical phenomenon of potential internal conflicts to the free cash flow of the company and its use for the benefit of increasing corporate value. Such internal conflicts require an appropriate settlement so as not to affect the company's failure. This study examines the role of dividend policy and ownership structure in moderating the relationship between free cash flow and firm value on manufacturing companies listed on BEI as many as 236 companies using randon sampling method. Free cash flows, profitability, firm size have a significant effect on company value while company growth has no significant effect. Dividends and majority ownership and managerial moderate free cash flow against corporate value. The results of this study are expected to generate alternative solutions to free cash flow problems and increase the value of the company.